How minimally invasive vestibular neurotomy for incapacitating Meniere's disease improves dizziness and anxiety. (3rd July 2017) - Miyazaki, Hidemi; Nomura, Yasuyuki; Mardassi, Ali; Deveze, Arnaud; Miura, Masahiro; Jike, Maki; Magnan, Jacques
Abstract: Conclusion: Patients with incapacitating Meniere Disease (MD) suffer in their daily lives and activities because of the dizziness and anxiety induced by MD. Minimally Invasive Vestibular Neurotomy (MIVN) is a safe and effective surgical treatment for these individuals, and improved their dizziness and anxiety. Objectives: This study aimed to assess the state of dizziness and anxiety of patients with incapacitating MD and its improvement through MIVN. Method: A total of 118 patients with incapacitating MD who underwent MIVN in France and Japan were evaluated. The DHI (Dizziness Handicap Inventory), SAST (Short Anxiety Screening Test), and STAI (State Trait Anxiety Index) questionnaires were used to evaluate disequilibrium and anxiety. Results: The MIVN method appears safe and effective for patients with incapacitating MD. Pre-operative assessment results by DHI and SAST were significantly related to each other, and were influenced by lifestyle and profession. This prospective study showed that MIVN improved dizziness and anxiety in these patients.